T Cell Reactivity against Mycolyl Transferase Antigen 85 of M. tuberculosis in HIV-TB Coinfected Subjects and in AIDS Patients Suffering from Tuberculosis and Nontuberculous Mycobacterial Infections. (22nd August 2010) - Launois, Pascal; Drowart, Annie; Bourreau, Eliane; Couppie, Pierre; Farber, Claire-Michèle; Van Vooren, Jean-Paul; Huygen, Kris
Abstract : The mycolyl transferase antigen 85 complex is a major secreted protein family from mycobacterial culture filtrate, demonstrating powerful T cell stimulatory properties in most HIV-negative, tuberculin-positive volunteers with latent M.tuberculosis infection and only weak responses in HIV-negative tuberculosis patients. Here, we have analyzed T cell reactivity against PPD and Ag85 in HIV-infected individuals, without or with clinical symptoms of tuberculosis, and in AIDS patients with disease caused by nontuberculous mycobacteria. Whereas responses to PPD were not significantly different in HIV-negative and HIV-positive tuberculin-positive volunteers, responses to Ag85 were significantly decreased in the HIV-positive (CDC-A and CDC-B) group. Tuberculosis patients demonstrated low T cell reactivity against Ag85, irrespective of HIV infection, and finally AIDS patients suffering from NTM infections were completely nonreactive to Ag85. A one-year follow-up of twelve HIV-positive tuberculin-positive individuals indicated a decreased reactivity against Ag85 in patients developing clinical tuberculosis, highlighting the protective potential of this antigen.